Determinants of Green Purchase Intention on Eco Print MSME Products in Surabaya - Marlena, Novi; Dwijayanti, Renny; Sudarwanto, Tri; Saino, Saino; Rahmadani, Rannu Dyah; Afifah, Siti Nur; Faharani, Alifia Annisa (International Journal of Emerging Research and Review, 2025)
Objective: This study aims to examine the impact of green perceived quality on green purchase intention. Additionally, it seeks to explore whether green trust enhances the relationship between green perceived quality and green purchase intention. Method: The research employs a quantitative approach, focusing on consumers in Surabaya who have experience purchasing eco-print products from MSMEs. A total of 300 respondents were selected using a simple random sampling technique. Data were collected through an online questionnaire distributed via Google Forms, and the analysis was conducted using Moderated Regression Analysis (MRA). Results: The findings reveal that green perceived quality significantly influences green purchase intention. However, green trust does not moderate or strengthen the relationship between green perceived quality and green purchase intention.  Novelty: While prior studies have investigated issues related to trust, this research uniquely examines the role of environmental beliefs from the perspective of perceived quality in shaping green purchase behaviour, particularly in the context of MSME products. By proposing a research framework, this study provides insights that can assist MSMEs in enhancing green purchasing intensity through strategies centered on green perceived quality and moderated by green beliefs.